2021
DOI: 10.1021/acsami.0c22605
|View full text |Cite
|
Sign up to set email alerts
|

Geminal Dicationic Ionic Liquid-Based Freestanding Ion Membrane for High-Safety Lithium Batteries

Abstract: A freestanding ion membrane with high ionic conductivity, electrochemical compatibility, satisfactory strength, and safety is a goal pursued for advanced energy storage. Geminal dicationic ionic liquids (GDILs) are expected to be designed and synthesized as a basic building block for the target ionic conductors. Herein, we fabricated a GDIL-based flexible ion conductive material, which appears and behaves as a freestanding film, an ion membrane actually, denoted as iMembrane. The iMembrane presented high therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In this context, geminal dicationic ionic liquids (GDILs) are thought to be a good candidate due to their higher thermal and chemical stability than many MILs. In fact, it has also been shown that the properties of GDILs are superior than the MILs in terms of the higher glass transition temperature, higher surface tension, and larger electrochemical window . We note that, due to the large electrochemical window (4.3 V to 4.7 V) of the GDILs, an electrolytic system comprising of GDILs and lithium-ion is expected to be beneficial in improving the electrochemical stability of the electrolytic medium at higher voltages. All these properties make GDILs as an attractive electrolytic medium for high-temperature batteries and dye sensitized solar cells despite the fact that they have high density . Since the above discussions depict many of the previous works that have been carried in understanding the behavior of MILs in the absence and presence of lithium-ion, studies on this aspect by employing GDILs are expected to be interesting.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this context, geminal dicationic ionic liquids (GDILs) are thought to be a good candidate due to their higher thermal and chemical stability than many MILs. In fact, it has also been shown that the properties of GDILs are superior than the MILs in terms of the higher glass transition temperature, higher surface tension, and larger electrochemical window . We note that, due to the large electrochemical window (4.3 V to 4.7 V) of the GDILs, an electrolytic system comprising of GDILs and lithium-ion is expected to be beneficial in improving the electrochemical stability of the electrolytic medium at higher voltages. All these properties make GDILs as an attractive electrolytic medium for high-temperature batteries and dye sensitized solar cells despite the fact that they have high density . Since the above discussions depict many of the previous works that have been carried in understanding the behavior of MILs in the absence and presence of lithium-ion, studies on this aspect by employing GDILs are expected to be interesting.…”
Section: Introductionmentioning
confidence: 96%
“…38−40 All these properties make GDILs as an attractive electrolytic medium for hightemperature batteries and dye sensitized solar cells despite the fact that they have high density. 41 Since the above discussions depict many of the previous works that have been carried in understanding the behavior of MILs in the absence and presence of lithium-ion, studies on this aspect by employing GDILs are expected to be interesting. Moreover, as reported earlier introduction of lithium-ion to the IL medium can cause significant changes in the structure and dynamics of the concerned media and all these matters are all intricately related to the performance of a suitable electrolytic medium in the lithium-ion battery.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6a). 52 Fig. S13 † presents the CV measurement of the NCM622kLi cell, which demonstrated that the battery has a stable redox potential.…”
mentioning
confidence: 99%
“…PPL-IL obtains a lower ion barrier, which is proved by the lower Ea. The improving electrochemical performance is attributed to PFIL, which decreases crystallinity and enhances the mobility of Li + . , Ionic conductivity, activation energy, and Li + transference numbers are shown in Table S3.…”
Section: Resultsmentioning
confidence: 99%